Synthesis of dense porous layered double hydroxides from struvite - Kwok, WLJ; Suo, H; Chen, C; Leung, DWJ; Buffet, J-C; O'Hare, D (Royal Society of Chemistry, 2021)
We report an atom economic synthesis of a new type of dense porous layered double hydroxides (SLDHs) using struvite which is a commonly produced undesirable waste in wastewater treatment plants. The obtained SLDHs exhibit significantly higher specific surface areas and larger pore volumes than conventional coprecipitated LDHs but retain a comparable particle density.